Transition readiness and anxiety among adolescents with a chronic condition and their parents: A cross-sectional international study - Tornivuori Anna; Kallio Mira; Culnane Evelyn; Pasanen Mira; Salanterä Sanna; Sawyer Susan; Kosola Silja (United States, 2025)
Aims
To evaluate associations of age, transition readiness and anxiety in adolescents with chronic conditions and to compare perceptions of adolescents and their parents regarding health self-management and transition readiness.
Design
Cross-sectional international study, reported following STROBE guidelines.
Methods
Adolescents and young adults (N = 512, mean age 17.7) with a chronic medical condition and their parents (N = 322) from Finland and Australia. Data were collected through surveys (between September 2017 and December 2020).
Adolescents reported the duration of their condition. Age at survey was defined by the response date of the questionnaires. Validated questionnaires were used to measure transition readiness (Am I ON TRAC? for Adult Care) and anxiety related to transition of care (State–Trait Anxiety Inventory short form). Perceptions of health self-management and transition readiness were compared in adolescent/parent dyads. Associations were explored using Spearman's correlation.
Results
Duration of condition and age at survey correlated weakly with transition readiness knowledge and behaviour. Higher transition readiness knowledge scores correlated with higher behaviour scores. Higher transition readiness behaviour scores were associated with lower levels of anxiety. Adolescents were less anxious than their parents and adolescents and parents mostly agreed about health self-management and transition readiness.
Conclusion
Transition readiness should be determined by an assessment of knowledge, self-management and psychosocial skills instead of age alone. Further research should address how well transition readiness predicts positive health outcomes after the transfer of care.
Implications for Patient Care
Transition readiness and self-management skills should be formally assessed because positive feedback may decrease the anxiety of both adolescents and their parents regarding the transfer of care.
Reporting Method
We have adhered to the STROBE statement, using STROBE checklist for cross-sectional studies.
Patient or Public Involvement Statement
No patient or public involvement.
Trial and Protocol Registration
ClinicalTrials.org NCT04631965.